An Electronic Bus Bar Lies in the Core of Cytochrome bc(1) - Świerczek, Monika (2010)
The ubiquinol–cytochrome c oxidoreductases, central to cellular respiration and photosynthesis, are homodimers. High symmetry has frustrated resolution of whether cross-dimer interactions are functionally important. This has resulted in a proliferation of contradictory models. Here, we duplicated and fused cytochrome b subunits, and then broke symmetry by introducing independent mutations into each monomer. Electrons moved freely within and between monomers, crossing an electron-transfer bridge between two hemes in the core of the dimer. This revealed an H-shaped electron-transfer system that distributes electrons between four quinone oxidation-reduction terminals at the corners of the dimer within the millisecond time scale of enzymatic turnover. Free and unregulated distribution of electrons acts like a molecular-scale bus bar, a design often exploited in electronics.